Pohjois-Savon kilpailukyky ja tulevaisuuden haasteet: Selvitys Pohjois-Savon liitolle - Hannu Hernesniemi; Martti Kulvik; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2012)
– The turnover of the companies in North Savo in 2011 was nearly 10 billion euros, of which industry accounted for just under a third. The industrial structure of the region is not strong, but on the other hand it is not alarmingly thin either, because it does have certain successful niches. North Savo's production and export growth has been on par with the average of other regions. The region is specialized in forestry and machinery industries as well as food production. The forest and machinery industries are export-oriented. Promising growth businesses include biopharmaceutical research, testing and production. These segments will be the engines of growth for the region in the future. In the forest industry the wood products industry is strong and its special products, such as heat treated wood, glue-laminated timber and hardwood floors, are selling well. Pulp and paper production have suffered losses, but the carton is in demand. In the machinery industry, power plant boilers, forestry tractors and mining machinery are global successes. Their production networks include a considerable number of local sub-contractors. Counterflow strategies will be the key to future development. The forest industry will evolve into a biotechnology industry, where decentralized local bio-oil production instead of large plants will play a large role. Clusters can be built around wooden apartment buildings. The key skills of the machinery industry should be kept as Savo's own secret, but the network of services and output should go global. In addition to timber, milk is one of the region's precious raw materials, the production of which should be safeguarded in the future. Research can facilitate processing of milk and timber into more lucrative products with higher value-added. Fresh, local and organic food production can be promoted via entrepreneurial training, product development, and use of competitive bidding in purchases of fresh food products by public institutions. Development of the pharmaceutical industry is following a dual strategy: the development of the biopharmaceutical industry is based on synergies and investing in research, entrepreneurship and the raising of risk capital. Neighbouring Russia is investing in the development of its pharmaceutical industry. Kuopio's medical cluster could participate by helping in the development of medicines, approval process, manufacturing and packaging, as well as marketing to Western markets. Industrial development requires close-knit co-operation with government departments. The University of Eastern Finland, the Savonia University of Applied Sciences, vocational schools, research institutes and laboratories, Kuopio University Hospital and the Finnish Medicines Agency as well as authorities responsible for business development and funding are key players is this development.
Keywords: R11; D28; R53; L52; L73; L66; L61; L62; L64; L65; 330; North Savo; regional economy; competitiveness; industrial policy; forest products; food industry; machinery and metal manufacturing; pharmaceuticals and biotechnology